2009
DOI: 10.1080/02701367.2009.10599563
|View full text |Cite
|
Sign up to set email alerts
|

Intrateam Communication and Performance in Doubles Tennis

Abstract: Verbal and nonverbal communication is a critical mediator of performance in team sports and yet there is little extant research in sports that involves direct measures of communication. Our study explored communication within NCAA Division I female tennis doubles teams. Video and audio recordings of players during doubles tennis matches captured the communications that took place between and during points. These recordings were coded and sequential analysis computed using the Discussion Analysis Tool software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 12 publications
4
45
0
1
Order By: Relevance
“…This result is consistent with other findings (Foushee & Manos, 1981;Lausic et al, 2009;Mosier & Chidester, 1991;Orasanu, 1990;), which suggest that frequent use of communication patterns facilitates performance through the enhancement of within team coordination (see Eccles & Tenenbaum, 2004) …”
Section: Differences Between Winning and Losing Teamssupporting
confidence: 94%
See 2 more Smart Citations
“…This result is consistent with other findings (Foushee & Manos, 1981;Lausic et al, 2009;Mosier & Chidester, 1991;Orasanu, 1990;), which suggest that frequent use of communication patterns facilitates performance through the enhancement of within team coordination (see Eccles & Tenenbaum, 2004) …”
Section: Differences Between Winning and Losing Teamssupporting
confidence: 94%
“…Consistent with the previous findings (Bowers, Jentsch, Salas, & Braun, 1998;Lausic et al, 2009), winning teams used substantially higher number of action statements than losing teams. In fact, action → action patterns may have yielded significant benefits for winning teams as the players in these teams used these communication patterns twice as many times when winning than losing.…”
Section: Differences Between Winning and Losing Close Games For Winnisupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the team's success is just as dependent on the effective communication between the coxswain and the rowers as it is on the physical abilities of the rowers. Studies have begun to delve into the importance of communication for improving team performance in sports (e.g., Lausic et al, 2009;Sullivan & Feltz, 2003). For instance, Lausic et al (2009) found that more successful doubles tennis teams engaged in a greater frequency of information exchange and also utilized more action plan statements during matches (e.g., talking about the upcoming rally: 'I'll serve it wide and you make a fake move to the net') compared to less successful teams who had more task-irrelevant statements (e.g., 'this shoe is driving me crazy').…”
Section: Regulation Of Team Performancementioning
confidence: 99%
“…Studies have begun to delve into the importance of communication for improving team performance in sports (e.g., Lausic et al, 2009;Sullivan & Feltz, 2003). For instance, Lausic et al (2009) found that more successful doubles tennis teams engaged in a greater frequency of information exchange and also utilized more action plan statements during matches (e.g., talking about the upcoming rally: 'I'll serve it wide and you make a fake move to the net') compared to less successful teams who had more task-irrelevant statements (e.g., 'this shoe is driving me crazy'). While communication patterns in terms of both quantity and quality will vary across sports, studies from organizational settings as well as recent research in sport clearly show that effective communication is vital for successful team performance.…”
Section: Regulation Of Team Performancementioning
confidence: 99%